The prognostic value of serum apolipoprotein A1 levels in elderly patients with de novo SARS-CoV-2 omicron infection - Shi, Cong; Ma, Ruishuang; Zhou, Miao; Yang, Shujun; Gong, Shengping (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe coronavirus disease of 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2, has affected millions of people worldwide. The omicron variant is currently the predominant strain circulating worldwide. Serum apolipoprotein A1 (ApoA1) is linked to endothelial cell injury and serves as a valuable biomarker for monitoring the progression of inflammation in infected individuals. However, the potential roles of ApoA1 in the context of the omicron variant remain elusive.MethodsTo investigate the prognostic value of serum ApoA1 levels at diagnosis, using mortality rate as the primary evaluation indicator, we performed a 65-day monitoring and retrospectively analyzed a cohort of 237 individuals diagnosed with omicron. Patients were categorized into two groups based on their ApoA1 levels, high and low. The Kaplan-Meier method was employed to assess overall survival (OS), while the log-rank test was utilized for comparative analysis between the groups. Additionally, both univariate and multivariate Cox proportional hazards models were applied to evaluate the prognostic significance of ApoA1 levels.ResultsOur results indicated that ApoA1 levels were significantly reduced in patients infected with the omicron variant. Notably, ApoA1 levels in severe cases were lower than those in mild-to-moderate cases, with this difference reaching statistical significance. Additionally, we observed a significant increase in C-reactive protein (CRP) and beta-2 microglobulin (β2-MG) levels in individuals with decreased ApoA1 levels. Furthermore, patients with reduced ApoA1 levels exhibited a statistically significant decline in OS (P = 0.001). A decreased ApoA1 level (< 0.87 g/L) was identified as an independent adverse prognostic factor for OS in omicron patients, as determined by multivariate cox proportional hazards regression analysis (P = 0.035).ConclusionThe serum ApoA1 level at the initial diagnosis was significantly correlated with the severity and prognosis of omicron infections. Therefore, we propose that decreased levels of ApoA1 may serve as an independent negative prognostic factor in patients infected with omicron.